2015
DOI: 10.1109/jphot.2015.2486683
|View full text |Cite
|
Sign up to set email alerts
|

Soliton Trapping of Dispersive Waves in Photonic Crystal Fiber With Three Zero-Dispersive Wavelengths

Abstract: Soliton trapping of dispersive waves during supercontinuum generation in the photonic crystal fiber with three zero-dispersion wavelengths, which is pumped by femtosecond pulses, is numerically studied. It is demonstrated that the generated supercontinuum is bounded by two branches of dispersive waves, namely, soliton-like dispersive wave and red-shifted dispersive wave (R-DW). When the R-DW with low intensity is generated in the marginal normal dispersion regime, the soliton-like dispersive wave with high int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…For the numerical model of ultra-short pulse propagation in a PCF with three ZDWs, a well-known and universally used NLSE can be described as (1) The NLSE has been described in detail elsewhere [15,25], but here we consider a brief description in pursuit of completeness. In Eq.…”
Section: Numerical Modelmentioning
confidence: 99%
“…For the numerical model of ultra-short pulse propagation in a PCF with three ZDWs, a well-known and universally used NLSE can be described as (1) The NLSE has been described in detail elsewhere [15,25], but here we consider a brief description in pursuit of completeness. In Eq.…”
Section: Numerical Modelmentioning
confidence: 99%
“…[9,19] Previous papers mainly focused on the SST effect as a spectral switching phenomenon occurring in the fiber with different dispersion profiles. [17,[19][20][21] For example, Poletti et al numerically demonstrated the SST effect in an index-guiding holey fiber with a tunable GVD barrier over a wide wavelength span. [19] In another work, Wang et al showed a cascaded SST effect in segmented fibers with engineered dispersion, which can lead the soliton pulse to transfer over a wide wavelength span.…”
Section: Introductionmentioning
confidence: 99%
“…[20] There have been many studies indicating that initial chirp can exert an influence on both fundamental solitons and DWs in SC generation. [21][22][23][24][25] For example, Lei et al showed how to conveniently and efficiently manipulate the DW generation by controlling the prechirp of the input pulse. [14] In addition, Cheng et al proved that there exists an optimal positive chirp maximizing the spectral bandwidth.…”
Section: Introductionmentioning
confidence: 99%